SELF-PLAGIARISM IN MANUSCRIPTS SUBMITTED TO A SCIENTIFIC JOURNAL: RECOMMENDATIONS ON FORMULATION OF THE EDITORIAL POLICY - Ruslan Т. Saygitov ("Paediatrician" Publishers LLC, 2017)
Self-plagiarism  is one of the most controversial  issues faced by participants in the publication process (authors, editors, reviewers). The article presents a brief analysis on the professional editorial communities' position on the problem. We give both comments and recommendations on formulation of the academic journal editorial policy. The paper provides the examples when the self-plagiarism is acceptable (minor copying of a few sentences, source fully and clearly referenced). In addition, it is pointed out that self-plagiarism can bear reputational and legal risks to an academic journal. Authors should consider this aspect when interacting with editors and reviewers.